2016
DOI: 10.1124/dmd.115.068569
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protein-Protein and Protein-Membrane Interactions on P450 Function

Abstract: This symposium summary, sponsored by the ASPET, was held at Experimental Biology 2015 on March 29, 2015, in Boston, Massachusetts. The symposium focused on: 1) the interactions of cytochrome P450s (P450s) with their redox partners; and 2) the role of the lipid membrane in their orientation and stabilization. Two presentations discussed the interactions of P450s with NADPH-P450 reductase (CPR) and cytochrome b 5 . First, solution nuclear magnetic resonance was used to compare the protein interactions that facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 95 publications
(97 reference statements)
1
26
0
1
Order By: Relevance
“…whether the copurified proteins were in direct physical interactions or in spatial proximity with the baits, our study revealed several electron transfer proteins that coeluted with monolignol P450 enzymes (Table 1). This discovery coincides with the previous demonstration that mammalian and human microsomal P450s physically interact with their redox partners, CPR and CB5, via electrostatic interactions at the basic, positively charged proximal surfaces of P450s (Schenkman and Jansson, 1999;Im and Waskell, 2011;Kandel and Lampe, 2014;Scott et al, 2016). The interaction of P450 with its electron carrier was proposed to form a functional 1:1 complex (Miwa and Lu, 1984).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…whether the copurified proteins were in direct physical interactions or in spatial proximity with the baits, our study revealed several electron transfer proteins that coeluted with monolignol P450 enzymes (Table 1). This discovery coincides with the previous demonstration that mammalian and human microsomal P450s physically interact with their redox partners, CPR and CB5, via electrostatic interactions at the basic, positively charged proximal surfaces of P450s (Schenkman and Jansson, 1999;Im and Waskell, 2011;Kandel and Lampe, 2014;Scott et al, 2016). The interaction of P450 with its electron carrier was proposed to form a functional 1:1 complex (Miwa and Lu, 1984).…”
Section: Discussionsupporting
confidence: 88%
“…Cytochrome P450 enzymes physically and stochastically associate with their redox partner CPR or CB5 via electrostatic interactions to form functional 1:1 complexes (Vergéres and Waskell, 1995;Backes and Kelley, 2003;Im and Waskell, 2011;Scott et al, 2016). Such redox partner-enzyme complex formation is essential for the roles of P450 enzymes in xenobiotic detoxification and drug metabolism in mammals (Kandel and Lampe, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic cycle of P450 enzymes depends on redox partners for electron delivery. The NADPH-cytochrome P450 reductase (CPR) is strictly required for the activity of microsomal P450s, while cytochrome b 5 can potentially be a donor molecule, albeit only for the second electron transfer step ( Scott et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three types of interactions are involved in adsorption of enzyme onto lignin: (i) hydrophobic interactions (Ying et al 2018;Tokunaga et al 2019); (ii) electrostatic interactions (Nakagame et al 2011;Scott et al 2016), and (iii) hydrogen-bonding (Rahikainen et al 2013;Liu et al 2016). The CBDs of T. reesei cellulases, Cel7A and Cel5A were adsorbed onto lignin in significantly high amount (Yarbrough, et al 2015;Liu et al 2016) due to hydrophobic interaction.…”
Section: Interactions Between Enzyme and Materials Surfaces At The Molmentioning
confidence: 99%